Effects of phosphodiesterase V inhibition alone and in combination with BNP on cardiovascular and renal response to volume load in human preclinical diastolic dysfunction. Issue 16 (17th August 2021) - Wan, Siu‐Hin; McKie, Paul M.; Slusser, Joshua P.; Burnett, John C.; Hodge, David O.; Chen, Horng H.
Abstract: Preclinical diastolic dysfunction (PDD) results in impaired cardiorenal response to volume load (VL) which may contribute to the progression to clinical heart failure with preserved ejection fraction (HFpEF). The objective was to evaluate if phosphodiesterase V inhibition (PDEVI) alone or combination PDEVI plus B‐type natriuretic peptide (BNP) administration will correct the impaired cardiorenal response to VL in PDD. A randomized double‐blinded placebo‐controlled cross‐over study was conducted in 20 subjects with PDD, defined as left ventricular ejection fraction (LVEF) >50% with moderate or severe diastolic dysfunction by Doppler echocardiography and without HF diagnosis or symptoms. Effects of PDEVI with oral tadalafil alone and tadalafil plus subcutaneous (SC) BNP, administered prior to acute volume loading, were assessed. Tadalafil alone did not result in improvement in cardiac response to VL, as measured by LVEF, LV end diastolic volume, left atrial volume (LAV), or right ventricular systolic pressure (RVSP). Tadalafil plus SC BNP resulted in improved cardiac response to VL, with increased LVEF (4.1 vs. 1.8%, p  = 0.08) and heart rate (4.3 vs. 1.6 bpm, p  = 0.08), and reductions in both LAV (−4.3 ± 10.4 vs. 2.8 ± 6.6 ml, p  = 0.03) and RVSP (−4.0 ± 3.0 vs. 2.1 ± 6.0 mmHg, p  < 0.01) versus tadalafil alone. Plasma and urinary cyclic guanosine monophosphate (cGMP) excretion levels were higher (11.3 ± 12.3 vs. 1.7 ± 3.8 pmol/ml, 1851.0 ± 1386.4 vs. 173.4 ± 517.9 pmol/min, p  < 0.01) with tadalafil plus SC BNP versus tadalafil alone. There was no improvement in renal response as measured by GFR, renal plasma flow, sodium excretion, and urine flow with tadalafil plus SC BNP compared to tadalafil alone. In subjects with PDD, tadalafil alone resulted in no improvement in cardiac adaptation, while tadalafil and SC BNP resulted in enhanced cardiac adaptation to VL. Trial Registration: ClinicalTrials.gov NCT01544998.